Recombinant Human Adenovirus Type 5 (H101) Intra-Tumor Therapy in Patients with Persistent, Recurrent, or Metastatic Cervical Cancer: Genomic Profiling Relating to Clinical Efficacy - Zhang Q; Zhang J; Liu Z; Wang J; Wang F; Wang T; Shi F; Su J; Zhao Y (Dove Medical Press, 2023)
Qiying Zhang,1 Jing Zhang,1 Zi Liu,1,2 Juan Wang,1 Fei Wang,1 Tao Wang,1 Fan Shi,1 Jin Su,1 Yalong Zhao3 1Department of Radiation Oncology, the First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, 710061, People's Republic of China; 2Biobank, the First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, 710061, People's Republic of China; 3Department of Medical Affairs, Guangdong Techpool Bio-Pharma Co, Ltd, Guangzhou, 510000, People's Republic of ChinaCorrespondence: Zi Liu, Department of Radiation Oncology, the First Affiliated Hospital of Xi'an Jiaotong University, No. 277, West Yanta Road, Xi'an, Shaanxi, 710061, People's Republic of China, Tel +86-18991232167, Email liuzmail@126.comObjective: Genomic profiles relating to H101 treatment-induced alterations are yet to be achieved. Here, we evaluated the impact of H101 via exome-sequencing approaches aiming to probe for potential biomarkers that are actionable in the treatment of persistent/recurrent/metastatic (P/R/M) cervical cancer.Methods: Whole exome sequencing (WES) was performd on paired pre- and post-H101 samples from 17 P/R/M cervical cancer patients who received serial intra-tumor injections of H101. Somatic mutations, including high-frequency mutations, microsatellite instability (MSI) status, tumor mutation burden (TMB), clonal evolution, and mutational signature were analyzed.Results: The median follow-up time after the H101 treatment was 14 months. Complete response was achieved in 9 patients, 3 patients achieved partial response, and 2 patients had stable disease, resulting in an objective response rate (ORR) of 70.6% (95% CI: 46.4%-96.7%). WES analysis showed no difference in treatment-related mutation characteristics, including non-synonymous-SNVs and TMB status. Patients with lower TMB were correlated with improved H101 response rates (P=0.044), whereas the same was not evident in high MSI (MSI-H) versus non-MSI-H patients (P=0.528). We observed a few high-frequency mutation genes (TTN, KMT2D, ALDOA, DNAH7, ADAP1, PTPN23, and THEMIS2) that probably carry functional importance in response to H101 treatment, among which KMT2D and ADAP1 mutations were associated with inferior progression-free survival (PFS) and/or overall survival (OS) (P< 0.05). Notably, H101 treatment-induced accumulating subclones or clusters in primary tumors and some (Signature 2) were associated with shorter PFS.Conclusion: We conducted an unprecedented work via a WES-based approach and provided preliminary insights into H101 treatment-induced genetic aberrations in which some genes (TTN, KMT2D, ALDOA, DNAH7, ADAP1, PTPN23, and THEMIS2) could be considered potential therapeutic targets of H101-containing treatment in cervical carcinoma. Moreover, the therapy-associated characteristics such as clonal evolution and a mutational signature may warrant further evaluation of H101 in clinical settings for treating cervical carcinoma.Keywords: cervical cancer, recombinant human adenovirus type 5, H101, whole exome sequencing, genomic profiling, therapeutic targets